REGENERAÇÃO NATURAL E BANCO DE SEMENTES EM FLORESTA OMBRÓFILA DENSA MONTANA PÓS-INCÊNDIO - Mores, Guilherme Jose (2020)
Fires are a major cause of habitat loss and biodiversity. Faced with this scenario, the affected areas find it more difficult to resume their functionality. Therefore, it is extremely important to know the mechanisms that will support restoration, as well